ANALYSIS OF EFFICIENCY, EFFECTIVENESS, POTENTIAL, AND CONTRIBUTION OF P2 PBB REVENUE TO PAD REGENCY BLITAR 2016-2021 - Oktavia, Siska Putri; Lutfllah, Novrida Qudsi; Ari Kamayanti (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Kristen Indonesia Paulus, 2023)
This research is aimed to analyze management of Rural and Urban Land and Building Tax (PBB P2) in Blitar Regency in 2016-2021. Qualitative research with descriptive analysis. Primary and secondary data were obtained through semistructured interview, documentation and observation. The results indicate that efficiency was 4.5% criterion very efficient. Effectiveness 106% was criterion very effective. The proportion ratio was 3.35 criterion prime criteria. The growth ratio was 0.12 in potential. Contribution was 10% criterion very poor category. Obstacle factors were human resources, budget, facilities and infrastructure, covid 19. Supporting factors were leadership, data updating, e-pbb, regulatory factors, taxpayer awareness, targeting.